2004
DOI: 10.1177/108925320400800109
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Inoperable Coronary Disease and Refractory Angina: Spinal Stimulators, Epidurals, Gene Therapy, Transmyocardial Laser, and Counterpulsation

Abstract: Intractable angina from refractory coronary disease is a severe form of myocardial ischemia for which revascularization provides no prognostic benefit. Inoperable coronary disease is also accompanied by a "vicious cycle" of myocardial dystrophy from a chronic alteration of the cardiac sympathetic tone and sensitization of damaged cardiac tissues. Several adjunctive treatments have demonstrated efficacy when revascularization is either unsuccessful or contraindicated. Spinal cord stimulation modifies the neurol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 97 publications
(125 reference statements)
0
7
0
4
Order By: Relevance
“…Meta-analysis showed that when compared to a no stimulation control, SCS significantly improved the exercise capacity and health-related quality of life of this patient population. The magnitude of outcome improvement with SCS appears to be similar to that of CABG and PMR, although the relevance of CABG as a treatment option for management of refractory angina is questionable [ 1 , 3 ]. A proportion of patients experienced SCS-related complications, in particular infections and lead migration or breakage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meta-analysis showed that when compared to a no stimulation control, SCS significantly improved the exercise capacity and health-related quality of life of this patient population. The magnitude of outcome improvement with SCS appears to be similar to that of CABG and PMR, although the relevance of CABG as a treatment option for management of refractory angina is questionable [ 1 , 3 ]. A proportion of patients experienced SCS-related complications, in particular infections and lead migration or breakage.…”
Section: Discussionmentioning
confidence: 99%
“…For this patient group, a number of non-conventional treatment options have emerged including, pharmacotherapy, enhanced external counterpulsation, percutaneous myocardial laser revascularisation (PMR), percutaneous coronary artery bypass (CABG), and spinal cord stimulation (SCS) [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with refractory angina pose treatment dilemmas for the cardiac treatment team, and are not adequately treated. Treatment options that have emerged for refractory angina pectoris include thoracic epidural injection, stellate ganglion blockade, enhanced external counterpulsation, percutaneous myocardial laser revascularization, transcutaneous electric nerve stimulation, and SCS [1,9]. …”
Section: Discussionmentioning
confidence: 99%
“…25,26 Further studies have found that HTEA HTEA attenuates the surgical stress response and stabilizes hemodynamics 4,27,28 after coronary artery bypass grafting (CABG). The impact on left ventricular function remains more controversial as this has been found to be improved, 2,26,[29][30][31] unchanged, 32 or even with severely reduced contractility. [33][34] However, the variability of these results might be due to different types of anesthetics, animal mingling with human studies, difference in level and number of blocked segments or variances in methods used to evaluate left ventricular function.…”
Section: Cardioprotection and Cardiovascular Performancementioning
confidence: 99%